Phenocam - Region Of Interest (ROI) Time Series from Lönnstorp Experimental Fields, Mast 10m Phenocam 03, 2022-01-24–2025-04-30 - Lönnstorp Research Station (Swedish University of Agricultural Sciences, 2025)
Daily aggregated time series containing solar-weighted mean vegetation indices and RGB channel values per Region of Interest, temporal data, solar metrics, and processing statistics for each daily composite.
Lönnstorp Research Station (2025). Phenocam - Region Of Interest (ROI) Time Series from Lönnstorp Experimental Fields, Mast 10m Phenocam 03, 2022-01-24–2025-04-30 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/rRm9c842FoWVfcW7GklRTavQ
Keywords: SITES Spectral; Calibration/Validation; Ecosystem functions; Plant Phenology; Reflectance; Vegetation Index; Time instant; Time instant; Day of the year; Day of the year; Daily averaged Green Chromatic Coordinate; Daily averaged Green Chromatic Coordinate; Daily averaged Red Chromatic Coordinate; Daily averaged Red Chromatic Coordinate; Daily averaged Blue Chromatic Coordinate; Daily averaged Blue Chromatic Coordinate; Daily weighted averaged value of Red Channel; Daily weighted averaged value of Red Channel; Daily weighted averaged value of Green Channel; Daily weighted averaged value of Green Channel; Daily weighted averaged value of Blue Channel; Daily weighted averaged value of Blue Channel; Number of images; Number of images; Solar-weighted mean sun elevation angle for daily aggregation; Solar-weighted mean sun elevation angle for daily aggregation; Maximum sun elevation angle; Maximum sun elevation angle; Solar-weighted mean solar zenith angle for daily aggregation; Solar-weighted mean solar zenith angle for daily aggregation; Solar-weighted mean absolute minutes from solar noon for daily aggregation; Solar-weighted mean absolute minutes from solar noon for daily aggregation; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap